Self‐regeneration of hairy vetch (Vicia villosa Roth) as affected by seedling density and soil tillage method in a semi‐arid agroecosystem - Renzi Pugni, Juan Pablo; Chantre Balacca, Guillermo Ruben; Cantamutto, Miguel Angel (2018)
Vicia villosa Roth is a forage legume with the capability for biological N fixation and natural reseeding, which could contribute to sustainability in semi‐arid regions. This study aimed to determine (i) the relationship between vetch density, seed production and spontaneous seed dispersal; (ii) the impact of the post‐dispersal tillage treatment over the soil seedbank dynamics; and (iii) potential predation of the seedbank by feral pigeons. A density range between 50 and 200 plants m−2 did not influence seed production or seed dispersal. Shallow disc tillage (SDT) clearly favoured self‐regeneration, resulting in higher amount of emerged seedlings during autumn compared to no tillage (NT). Based on observed emergence data, the percentage of emerged seedlings under SDT and NT were 38 and 6% of the seedbank, respectively, during 18 months after plot harvest. The lowest emergence values registered under NT could be associated with higher pressure from natural predators, soil‐borne pathogens, seed decay by ageing and false breaks. The feral pigeon (Columba livia var.) might be considered the main cause of vetch seedbank depletion in this study. Under controlled conditions, a single pigeon is able to consume, on average, between 184 and 768 seeds per day, depending on seed exposure and alternative food sources availability.